Narrative change in emotion-focused therapy: how is change constructed through the lens of the innovative moments coding system? - Mendes, Inês (2010)
The aim of this study was to advance understanding of how clients construct their own process of change in effective therapy sessions. Toward this end, the authors applied a narrative methodological tool for the study of the change process in emotion-focused therapy (EFT), replicating a previous study done with narrative therapy (NT). The Innovative Moments Coding System (IMCS) was applied to three good-outcome and three poor-outcome cases in EFT for depression to track the innovative moments (IMs), or exceptions to the problematic self-narrative, in the therapeutic conversation. IMCS allows tracking of five types of IMs events: action, reflection, protest, reconceptualization, and performing change. The analysis revealed significant differences between the good-outcome and poor-outcome groups regarding reconceptualization and performing change IMs, replicating the findings from a previous study. Reconceptualization and performing change IMs seem to be vital in the change process.